Making Ireland English : the Irish aristocracy in the seventeenth century - Ohlmeyer, Jane H. (Yale University Press, 2012)
"This ground breaking book provides the first comprehensive study of the remaking of Ireland's aristocracy during the seventeenth century. It is a study of the Irish peerage and its role in the establishment of English control over Ireland. Jane Ohlmeyer's research in the archives of the era yields a major new understanding of early Irish and British elite, and it offers fresh perspectives on the experiences of the Irish, English, and Scottish lords in wider British and continental contexts. The book examines the resident peerage as an aggregate of 91 families, not simply 311 individuals, and demonstrates how a reconstituted peerage of mixed faith and ethnicity assimilated the established Catholic aristocracy. Tracking the impact of colonization, civil war, and other significant factors on the fortunes of the peerage in Ireland, Ohlmeyer arrives at a fresh assessment of the key accomplishment of the new Irish elite: making Ireland English."--Publisher's description.